Phenotyping tools to dissect morphological diversity in sweet potato Ipomoea batatas (L.) Lam (2018)
Sweetpotato (Ipomoea batatas (L.) Lam.) is an hexaploid specie (2n=6x=90) with high levels of heterozygosity, it is an important tropical American crop belonging to the family Convolvulaceae (Austin and Huaman, 1996), which has wide variations in botanical characteristics and are readily distinguished on the basis of morphological traits, yield potential, size, shape, fresh and skin colour of roots, as well as sizes, colours and shapes of leaves and branches (Acheampong, 2012; Zhang et al., 2000).Morphological characterization has been used as a first step in assessment plant diversity for both plant genetic resources conservation and utilization (Mwanga et al., 2017). In thi study, new phenomic approaches were used to increase the e ciency discriminating di erent phenotypes not detected by conventional morphological descriptors.